Penerapan Metode Taguchi untuk Meningkatkan Kualitas Bata Ringan pada UD. XY Malang - Putri Halimah; Yurida Ekawati (JIEMS (Journal of Industrial Engineering and Management Systems), 2020)
Light brick compressive strength produced by UD. XY has a very high variation because there is no standard composition of raw materials. This research is carried out to design an improvement or quality improvement for light brick products at UD. XY. Quality improvement is on increasing the compressive strength of light brick with optimal composition. Quality improvement is conducted using the experimental design of the Taguchi method to obtain an optimal composition combination. The orthogonal array notation used is L9(34) with material control factors in the form of water (A), cement (B), and sand (C). Data processing is done by calculating ANOVA on average values and SNR with larger better classification. The classification is chosen because of the greater the compressive strength of the light brick the higher the quality of the light brick. This ANOVA calculation is carried out to find out which factors significantly influence the light brick compressive strength. The test conducted to determine the quality of light brick is a concrete compressive strength test carried out using the Compression Machine. Based on the results of data processing, a comparison of the optimal composition of water: cement: sand is 1: 2.5: 4. The confirmation experiment proves that the compressive strength of the composition is robust.